2007
DOI: 10.1002/jgm.1074
|View full text |Cite
|
Sign up to set email alerts
|

Acute intermittent porphyria: vector optimization for gene therapy

Abstract: These studies support the use of a gene therapy vector containing the alpha1Me/alpha1ATp combination for preclinical studies of the efficacy and safety of liver-targeted gene therapy for AIP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…All these data proffer some hope of cure for selected patients with severe forms of these diseases. To date, other therapeutic approaches, such as the infusion of recombinant porphobilinogen deaminase [49] or gene therapy have to be considered as experimental [29]; the latter approach has showed very good results in animal models of AIP, especially after the recent optimization of gene vectors [50].…”
Section: Prevention Of Attacksmentioning
confidence: 99%
“…All these data proffer some hope of cure for selected patients with severe forms of these diseases. To date, other therapeutic approaches, such as the infusion of recombinant porphobilinogen deaminase [49] or gene therapy have to be considered as experimental [29]; the latter approach has showed very good results in animal models of AIP, especially after the recent optimization of gene vectors [50].…”
Section: Prevention Of Attacksmentioning
confidence: 99%
“…In addition, although adenoviral vectors resulted in therapeutic HMB-synthase levels in experimental mice, its expression was transient, thus making them impractical for clinical applications [51]. Administration of recombinant adenoviral, AAV8-based andrecombinant AAV (rAAV) vectors in murine models containing the HMB-synthase complementary DNA, resulted in increased levels of hepatic HMB-synthase activity, inhibiting the phenobarbital-induced ALA and PBG accumulation and thus, indicating a potential for future gene therapy [51][52][53]. Finally, Johansson et al, 2003 and2002 showed in mammalian cells that non-viral gene delivery encoding HMB-synthase results in high expression of functional enzyme [54,55], suggesting enzymereplacement gene therapy as a feasible proposal.…”
Section: Acute Intermittent Porphyriamentioning
confidence: 99%